If p = , q = and r = , then verify that
(i) p × (q × r) = (p × q) × r
(ii) p × (q – r) = p × q – p × r
Solution:
More Solutions:
- Multiply and express the result in the lowest form
- Verify commutative property of multiplication for the following pairs of rational numbers
- Verify the following and name the property also
- Evaluate the following (2/5) x (-3/7) – (1/14) – (3/7) x (3/5)
- Fill in the following blanks
- Find the multiplication inverse of the following
- Find the sum of additive inverse and multiplicative inverse of 9.